58 RANCANGAN DIAGRAM KOMPONEN SISTEM REKAM MEDIS ELEKTRONIK - Rina Kurniawati; Septi Noer Lailela (POLITEKNIK PIKSI GANESHA, 2018)
Medical record is one of important information in health department. Medical record consists patient’s health notes and histories for each treatments they received in a health department. Medical record in most health provider in Indonesia including puskemasis still maintained conventionally. This condition is causing limitation compared tomedical record which maintained electronically, with hardware and software support. The design of electronic medical record system in this tofic will be implemented using J2EE framework, which based on three tiers architecture: presentation tier, business tier), and data tier.